Investigate the Quality of Production in The Sustainable Pavement Materials Industry - Sunarjono, Sri; Maulana, Nanang Sofa (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2020)
The cold mixture using emulsion asphalt has not been widely used due properties which is still low compared to the hot mixture. RAP (Reclaimed Asphalt Pavement) is a dismantling of old paved layers that are reused. RAP has not been widely used for mixed aggregates, because of the aggregates used wear are aging and fragile inversely proportional to fresh aggregates that have better surface and strength because they have not been used to withstand repetitive structural loads. The purpose of this study was to know the comparison of cold mixture asphalt emulsion properties using RAP and fresh aggregate materials by analyzing the volumetric characteristics, Marshall properties, and Indirect Tensile Strength (ITS) Properties. This cold asphalt emulsion mixture used RAP material from Weleri, Kendal and fresh aggregate from Woro river, Klaten. Asphalt emulsion type CSS-1 comes from PT.Izza Sarana Karsa, Sidoarjo. Variation of RAP addition to mixture are 0% RAP, 50% RAP, and 100% RAP. The gradation and mixed specifications used are Asphalt Concrete Wearing Course (AC-WC) Bina Marga 2010. The production of cold asphalt emulsion mixture started from the preparation of tools and materials, tested the aggregate characteristics, sieved the material, estimated the initial Emulsion Asphalt, mixed proportions, and solidification, determination of Optimum Residual Asphalt (ORAC), mixed test with Marshall test and modified ITS test. Based on results of the Marshall and ITS Properties from cold asphalt emulsion mixture used variation of RAP and fresh aggregate composition, that addition of RAP in mixture can increase density value and decrease air cavity this is proved by lower VIM and VMA value and higher VFWA value. As well, it decreases the value of Marshall Quotient and the value of indirect tensile strength. It is confirmed by the data from this study is 0% RAP yield density value 1,83 gr/cm3, 32,90% VMA, 19,90% VIM, 37,31% VFWA, 535,73 kg stability, 7,40 mm flow, 72.59 kg/mm MQ and the value of ITS 113,347 KPa. While 50% RAP yield density value 1,89 gr / cm3, 23,24% VMA, 10,75% VIM, 51,77% VFWA, 286,56 kg stability, 9,57 mm flow, 30,02 kg/mm MQ, and the value of ITS 87,919 KPa. And for 100% RAP has density value 1,91 gr / cm3, 13,42% VMA, 1,40% VIM, 86,78% VFWA, 300,92 kg stability, 13,50 mm flow, 23,73 kg/mm MQ and the value of ITS 95,293 KPa. Overall, the cold mixture does not fulfilling specifications for the manufacture of wearing course.